Profile of victims of accidents with biological material in a course of Dentistry - Fernanda Midori TSUZUKI; Bruna Angélica de Souza VIANA; Amanda Penha MATHIAS; Marcos Sérgio ENDO; Mitsue FUJIMAKI; Najara Barbosa da ROCHA (Faculdade São Leopoldo Mandic, 2019)
Objective: To identify the epidemiological profile of accidents with biological material occurring in the dental clinic of a university in the southern region of the country. Methods: This is a descriptive, cross-sectional, retrospective study, which analyzed the reports of the Epidemiological Surveillance (SINAN) that occurred between March 2013 and December 2016. We analyzed the demographic variables and data related to the notification of accidents with biological material in the SINAN file, such as: age, sex, race, occupation (student, teacher, oral health technician, residents), time and place of occurrence of the accident, agent causing the perforation, total or partial use of PPE (personal protective equipment) at the time of accident, contact with organic material, contact agent and up-to-date vaccination against hepatitis B and treatment withdrawal. The data obtained were analyzed in EpiInfo Software. Statistical analysis included descriptive and inferential analysis, with significance level of p?0.05 and confidence interval (CI) of 95%. Results: In total there were 55 reports of accidents with piercing-cutting materials, of which 12 were men (21.82%) and 43 were women (78.18%). The mean age of the sample population was 24.2 (± 6.3) years. Regarding the occupation, 80% (n = 44) were undergraduate students, 12.72% were residents, 5.45%, teachers and 1.82%, oral health technicians. The majority (61.8%) were perforated during the dental procedure, 21.82% during material washing and 16.36% during surgery, but 20% claimed that they did not use any personal protective equipment. Regarding the organic material, there was a high prevalence of contact with blood, 70.9%, the needle was the main agent (n = 26; 47.3%). Still, 3.7% stated that they were not vaccinated against hepatitis B. In the bivariate analysis, the site of the accident was associated with the use of personal protective equipment (p = 0.01). Conclusion: The results showed that the number of incidents is high and can be attributed to several factors, such as lack of experience of students and the non-use of personal protective equipment. As a result, it is necessary to establish a permanent education program focused on education and accident prevention strategies to minimize these problems.